Anaesthetic practices at Gulu Regional Referral Hospital in Northern Uganda, who does what and where? A retrospective study - Kutschke, N.; Lampe, J.; Hoepfner, O.; Kitara, D. L.; Schuster, A. (BioMed Central Ltd, 2025)
Hospitals such as the Gulu Regional Referral Hospital (GRRH) in northern Uganda, like many other regions of sub-Saharan Africa, lack the anaesthetists needed to provide adequate analgesia during surgical procedures. A retrospective review was conducted on surgical procedures and their anaesthetic management in three departments of GRRH during 2019. The possibility of performing pRA was determined based on the surgical site, infection status, and the type of surgical procedure being performed. A pRA was considered adequate when conditions for pRA were met and pRA was carried out. Chi-square test was used to compare categorical data. A bivariable logistic regression analysis was performed to identify the factors associated with the administration of peripheral regional anaesthesia and the qualifications of medical staff. A total of 804 procedures were recorded [67% in accident and emergency (A&E), 31% in operating room (OR), and 2% on the surgical ward]. Anaesthesia was recorded in 82% of cases. Of these, 86% were documented in regional and local anaesthesia. Anaesthetic officers carried out anaesthesia in 20% of all cases and in all cases in the operating room. HWs with more than 2 years of training performed adequate pRA more frequently than HWs with less than 1 year of experience [Odds ratio (OR) = 2.586; 95% CI 1.336-5.005; p = 0.005]. The last group, however, performed significantly more procedures in A&E than in other departments (89%, p < 0.001). The data show that pRA procedures are already used at GRRH, especially by HWs with high level of training in the OR. In A&E, which is primarily staffed by doctors with less than 1-year training, there is a potential to increase the administration of adequate pain relief by implementing simple nerve blocks into routine clinical practice. Therefore, doctors and staff in A&E would benefit from needs-based training in pRA.